Impact of occupational complexity on cognitive decline in the oldest-old. (2nd September 2021) - Hakiki, Bahia; Pancani, Silvia; Portaccio, Emilio; Molino-Lova, Raffaello; Sofi, Francesco; Macchi, Claudio; Cecchi, Francesca
Abstract: Objectives: The theory of "Cognitive Reserve" assumes that premorbid factors such as high educational and occupational attainment may enable a better way of coping with brain damage. It has been suggested that more stimulating lifestyles, including more complex work environments, may provide a buffer against cognitive decline in later life. This study aimed to investigate the association between occupational history and cognitive decline in a large cohort of Italian oldest-old. Methods: 392 individuals (266 women/126 men, mean age 93 ± 3 years) enrolled in the "Mugello study" provided information about their work history. Jobs were classified in nine categories, according to the level of expertise required to perform them, as suggested by the Italian National Institute for Statistics (ISTAT). In addition, socio-demographic characteristics, comorbidities, level of independence, depression, and cognitive status were assessed. The presence of dementia was established based on cognitive status and independence in performing four selected instrumental activities of daily living (ability to manage telephone, transportation, medications, and budget). Results: Neither work complexity ( p  = 0.995) nor work duration ( p  = 0.701) showed a significant effect on the likelihood of presenting a lower cognitive profile or developing dementia ( p  = 0.385 and p  = 0.096, for work complexity and work duration, respectively). Conclusion: In the observed sample of oldest-old individuals, cognitive decline did not seem to be influenced by cognitive reserve as assessed through the evaluation of cognitive status and level of independence. It is conceivable that in this population, the decline of the brain reserve has a preponderant role in the definition of the cognitive profile.